Speciation and Fluconazole Susceptibility of Candida Isolates from Clinical Samples in a Tertiary Hospital in Nepal - Sapkota, Jyotshna; Aryal, Kiran; Adhikari, Ram Prasad; Khadka, Sushila; Pandey, Ritu; Khanal, Laxmi Kant; Shrestha, Deepti; Sharma, Manisha (Journal of Institute of Medicine Nepal, 2024)
Introduction Candida species, commonly present as human commensals, are notable opportunistic pathogens responsible for superficial and invasive infections, particularly in hospitalized patients. This study aimed to characterize the distribution and antifungal susceptibility patterns of Candida species isolated from various clinical specimens at a tertiary care hospital in Nepal. Methods A descriptive cross-sectional, laboratory-based study was conducted in the Clinical Microbiology Laboratory of Nepal Medical College Teaching Hospital between July 2023 and June 2024. Clinical specimens yielding Candida species over the one-year period were included. Growth on Sabouraud dextrose agar was analyzed for colony morphology, Gram staining, germ tube production, and urea hydrolysis. Speciation of Candida isolates was performed using CHROMagar. Additionally, fluconazole susceptibility testing was conducted following Clinical and Laboratory Standards Institute guidelines. Results A total of 72 Candida isolates were identified from samples such as sputum, urine, and high vaginal swabs. Candida albicans was the most prevalent species 45 (62.5%), followed by non-albicans Candida (NAC) species, including C. glabrata 14 (19.4%), 9 C. tropicalis (12.5%), and 4 C. parapsilosis (5.6%). Fluconazole resistance was observed in 22.2% of total isolates of Candida, with C. glabrata exhibiting the highest resistance 12, (86%), whereas 4 (9%) of C. albicans demonstrated resistance to it. Conclusion The findings highlight a shift in epidemiology toward NAC species and raise concerns about rising fluconazole resistance. These results underscore the need for routine species identification and antifungal susceptibility testing to guide effective management strategies. The study advocates for antifungal stewardship programs and ongoing surveillance to address emerging resistance trends in Candida infections.